2014
DOI: 10.3382/ps.2014-04077
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism variants within tva and tvb receptor genes in Chinese chickens

Abstract: Avian leukosis is an immunosuppressive neoplastic disease caused by avian leukosis viruses (ALV), which causes tremendous economic losses in the worldwide poultry industry. The susceptibility or resistance of chicken cells to subgroup A ALV and subgroup B, D, and E ALV are determined by the receptor genes tumor virus locus A (tva) and tumor virus locus B (tvb), respectively. Four genetic resistant loci (tva(r1), tva(r2), tva(r3), and tva(r4)) in tva receptor gene and a genetic resistant locus tvb(r) in the tvb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Taken together, these studies show that the TVB*S1 allele is the common allele and that the TVB*R resistance allele is seldom observed in native chickens. Consistent with the results of analyses in Chinese [6,12,13] and Indian [11] domestic chicken breeds, the TVB*R allele was rarely observed in Turkish native breeds. These results are parallel to the observation that the TVB*R allele frequency in native chicken breeds is lower than that observed in WL populations [6] .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Taken together, these studies show that the TVB*S1 allele is the common allele and that the TVB*R resistance allele is seldom observed in native chickens. Consistent with the results of analyses in Chinese [6,12,13] and Indian [11] domestic chicken breeds, the TVB*R allele was rarely observed in Turkish native breeds. These results are parallel to the observation that the TVB*R allele frequency in native chicken breeds is lower than that observed in WL populations [6] .…”
Section: Discussionsupporting
confidence: 86%
“…Another study, conducted with a total of 1428 chickens from ten domestic Chinese breeds and 15 commercial broiler flocks, the frequencies of TVB*S1, TVB*S3, and TVB*R alleles varied between 0.71 and 0.91, 0.00 and 0.09, and 0.04 and 0.29, respectively. Eleven of the 25 breeds were homozygous for the TVB*S1 allele and five breeds of those had the TVB*R/R resistant genotype at varying frequencies (ranging from 0.03 to 0.15) [13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we identified intronic deletions of the tva receptor gene that result in reduced susceptibility to subgroup A ALVs (18). This finding is suggestive for the presence of similar genetic mutations within other ALV receptor genes, and Chinese broiler lines that have undergone long-term virus eradication measures may manifest such recessive alleles (30). Two tvb allelic variants were identified in Chinese commercial broiler lines by generating a series of amplicons for the genomic region of the tvb receptor gene followed by sequencing, which were designated the tvb r4 and tvb r5 alleles.…”
Section: Resultsmentioning
confidence: 73%
“…Thus, populations of chickens exposed to ALVs may be subjected to selection pressure, which mediates development of host complete or partial genetic resistance to ALV infection. In order to identify additional resistance alleles of ALV receptor loci, we systematically screened specific receptor genes in a panel of Chinese commercial broiler lines for naturally preexisting polymorphisms (30). We have previously identified two tva alleles causing reduced susceptibility to ALV-A infection that resulted from intronic deletions within the tva receptor gene (18).…”
mentioning
confidence: 99%